Pharmacological enhancement of cholinergic neurotransmission alleviates neuroinflammation and improves functional outcomes in a triple transgenic mouse model of Alzheimer’s disease - Munafò, Antonio; Cantone, Anna Flavia; Di Benedetto, Giulia; Torrisi, Sebastiano Alfio; Burgaletto, Chiara; Bellanca, Carlo Maria; Gaudio, Gabriella; Broggi, Giuseppe; Caltabiano, Rosario; Leggio, Gian Marco; Bernardini, Renato; Cantarella, Giuseppina (Frontiers in Pharmacology, 2024)
Introduction: Alzheimer's disease (AD) is the most common neurodegenerative disorder affecting the elderly population worldwide. Due to the multifactorial nature of the disease, involving impairment of cholinergic neurotransmission and immune system, previous attempts to find effective treatments have faced challenges. Methods: In such scenario, we attempted to investigate the effects of alpha-glyceryl-phosphorylcholine (α-GPC), a cholinomimetic molecule, on neuroinflammation and memory outcome in the triple transgenic mouse model of AD (3xTg-AD). Mice were enrolled at 4 months of age, treated orally with α-GPC dissolved in drinking water at a concentration resulting in an average daily dose of 100 mg/kg for 8 months and sacrificed at 12 months of age. Thereafter, inflammatory markers, as well as cognitive parameters, were measured. Results: Chronic α-GPC treatment reduced accumulation of amyloid deposits and led to a substantial re-balance of the inflammatory response of resident innate immune cells, astrocytes and microglia. Specifically, fluorescent immunohistochemistry and Western blot analysis showed that α-GPC contributed to reduction of cortical and hippocampal reactive astrocytes and pro-inflammatory microglia, concurrently increasing the expression of anti-inflammatory molecules. Whereas α-GPC beneficially affect the synaptic marker synaptophysin in the hippocampus. Furthermore, we observed that α-GPC was effective in restoring cognitive dysfunction, as measured by the Novel Object Recognition test, wherein 3xTg-AD mice treated with α-GPC significantly spent more time exploring the novel object compared to 3xTg-AD untreated mice. Discussion: In conclusion, chronic treatment with α-GPC exhibited a significant anti-inflammatory activity and sustained the key function of hippocampal synapses, crucial for the maintenance of a regular cognitive status. In light of our results, we suggest that α-GPC could be exploited as a promising therapeutic approach in early phases of AD.